High-intensity fire experiments to manage shrub encroachment: lessons learned in South Africa and the United States. Issue 1 (2nd January 2022) - Scholtz, Rheinhardt; Donovan, Victoria M; Strydom, Tercia; Wonkka, Carissa; Kreuter, Urs P; Rogers, William E; Taylor, Charles; Smit, Izak PJ; Govender, Navashni; Trollope, Winston; Fogarty, Dillon T; Twidwell, Dirac
Abstract : Human alteration of fire regimes is a hallmark of the Anthropocene; yet few studies have fully explored the implications of utilizing high-intensity fires in grasslands and savannas to manage shrub encroachment. Decades of fire research in South Africa inspired a unique convergence of high-intensity fire experiments in the USA. In the Great Plains of North America, high-intensity fire trials were designed to remove traditional investigator constraints that minimised variability in fire intensity and to explore woody mortality thresholds across a broader suite of experimental conditions. At the same time, studies in the Kruger National Park, South Africa, similarly investigated high-intensity fires to examine previously unstudied relationships between high-intensity fires and woody encroachment. These scientific pursuits have contributed to theoretical advances in our understanding of fire-vegetation dynamics. In this paper, we synthesise these high-intensity fire experiments, the empirical evidence emerging from them and their importance for managing grassland and savanna ecosystems, and the lessons learned and challenges ahead to maintaining critical ranges of variation in fire regimes during the Anthropocene.